Childhood trauma, alexithymia, and mental states recognition among individuals with alcohol use disorder and healthy controls. (1st December 2020) - Kopera, Maciej; Zaorska, Justyna; Trucco, Elisa M.; Suszek, Hubert; Kobyliński, Paweł; Zucker, Robert A.; Nowakowska, Malwina; Wojnar, Marcin; Jakubczyk, Andrzej
Highlights: Alexithymia was tested as a mediator between trauma and mental states recognition. Interactions between AUD and alexithymia on mental states recognition was tested. Findings provide support for moderated mediation. Emotional trauma impacts mental states recognition via alexithymia only in healthy adults. Abstract: Background: Although prior work indicates a link between childhood trauma, alexithymia, and mental states recognition, empirical support is limited. Moreover, findings based on adult samples are mixed. Previous studies demonstrate that childhood trauma might either enhance, preserve, or reduce mental states recognition in selected at-risk populations. The current study investigates whether alcohol use disorder (AUD) status moderates the association between childhood trauma, alexithymia, and mental states recognition in a treatment-seeking AUD sample and non-AUD healthy adults. Methods: Data comes from 255 individuals participating in an ongoing project that compares emotional and behavioral functioning of patients treated in an inpatient setting for AUD and a comparison sample of 172 healthy controls (HCs). Mental states recognition was measured using a computerized version of the Reading the Mind in the Eyes Task (RMET). The presence of childhood trauma was assessed with the Childhood Trauma Questionnaire. Alexithymia was measured with the Toronto Alexithymia Scale (TAS-20). Demographic information, as well as alcohol drinking and psychopathological symptoms were assessed. A moderated mediation model was estimated whereby alexithymia was included as a mediator in the association between childhood trauma and RMET performance, with AUD diagnosis status moderating the link between alexithymia and RMET performance. Results: Findings provide support for moderated mediation. Childhood emotional trauma impacted negative mental states recognition performance via difficulty describing feelings, but only among HCs ( p < 0.01). Conclusions: Findings highlight the impact that AUD status has on the association between early life emotional trauma and difficulty describing feelings on individual differences in mental states recognition.